Research advances in the structures and biological activities of secondary metabolites from Talaromyces - Lei, Li-Rong; Gong, Lei-Qiang; Jin, Meng-Ying; Wang, Rui; Liu, Ran; Gao, Jing; Liu, Meng-Dan; Huang, Li; Wang, Guang-Zhi; Wang, Dong; Deng, Yun (Frontiers in Microbiology, 2022)
The genus Talaromyces belongs to the phylum Ascomycota of the kingdom Fungi. Studies have shown that Talaromyces species yield many kinds of secondary metabolites, including esters, terpenes, steroids, alkaloids, polyketides, and anthraquinones, some of which have biological activities such as anti-inflammatory, bacteriostatic, and antitumor activities. The chemical constituents of fungi belonging to the genus Talaromyces that have been studied by researchers over the past ten years, as well as their biological activities, are reviewed here to provide a reference for the development of high-value natural products and innovative uses of these resources.